Evaluation of empiric therapy appropriateness, resistance patterns, and mortality in Pseudomonas aeruginosa infections in Jordan - Savana Sobh; Rania Itani; Khawla Abu Hammour; Rana K. Abu-Farha (Exploration of Medicine)
Aim: This study aimed to investigate the susceptibility patterns of Pseudomonas aeruginosa strains, examine infection characteristics, and evaluate the appropriateness of empiric antibiotic therapy. Additionally, the study sought to identify factors influencing 30-day all-cause mortality in patients with Pseudomonas aeruginosa infections. Methods: This was a retrospective study conducted at Jordan University Hospital from January 2018 to March 2024. Adult patients (≥ 18 years) with confirmed Pseudomonas aeruginosa infections were included. Data were collected from medical records, focusing on demographics, infection characteristics, antibiotic treatment, and outcomes. The susceptibility patterns of Pseudomonas aeruginosa isolates were classified as multidrug-resistant (MDR) or non-MDR. Logistic regression was used to identify factors associated with 30-day mortality. Results: A total of 210 patients were included in the study, with 106 males (50.5%) and 104 females (49.5%). The majority of infections were community-acquired (n = 178, 84.8%), with the respiratory tract being the most common infection site (n = 81, 38.6%). Nearly half of the Pseudomonas aeruginosa isolates were MDR (n = 99, 47.1%). Empiric antibiotic therapy was administered to all patients, with imipenem-cilastatin (55.7%), vancomycin (35.7%), and piperacillin-tazobactam (26.7%) being the most commonly used antibiotics. Of the 210 patients, 32.4% (n = 68) received inappropriate empiric therapy. The 30-day all-cause mortality rate was 4.9% (n = 10). Multivariate analysis revealed that non-localized infections, such as bacteremia and sepsis, were strongly associated with increased mortality [adjusted odds ratio (AOR) = 17.455, P < 0.001]. Conclusions: This study highlights the high prevalence of MDR Pseudomonas aeruginosa infections, especially in community-acquired cases, and emphasizes the need for improved antimicrobial stewardship. The significant proportion of patients (32.4%) receiving inappropriate empiric therapy calls for better guidance in antibiotic prescribing practices. The key predictor of mortality was infection localization, indicating the importance of early intervention for systemic infections to reduce mortality rates.